2010
DOI: 10.1007/s00701-010-0610-0
|View full text |Cite
|
Sign up to set email alerts
|

The retrogasserian zone versus dorsal root entry zone: comparison of two targeting techniques of gamma knife radiosurgery for trigeminal neuralgia

Abstract: The RGZ targeting technique in the GKRS for TN had a better treatment success, with fewer bothersome complications compared to the DREZ target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Park and colleagues presented a study directly comparing 2 targeting locations in a total of 39 patients who underwent SRS with a mean follow-up of 32.8 months in the DREZ group and 16.5 months in the retrogasserian zone (RGZ) group. 15 A maximum dose with a range of 80-90 Gy was used for DREZ targeting and a range of 83 Gy to 90 Gy for RGZ targeting. The study identified no difference in the risk of postradiosurgical complications, but the authors did find a shorter response time in the RGZ group (4.1 weeks vs 6.4 weeks, p = 0.044).…”
Section: Discussionmentioning
confidence: 99%
“…Park and colleagues presented a study directly comparing 2 targeting locations in a total of 39 patients who underwent SRS with a mean follow-up of 32.8 months in the DREZ group and 16.5 months in the retrogasserian zone (RGZ) group. 15 A maximum dose with a range of 80-90 Gy was used for DREZ targeting and a range of 83 Gy to 90 Gy for RGZ targeting. The study identified no difference in the risk of postradiosurgical complications, but the authors did find a shorter response time in the RGZ group (4.1 weeks vs 6.4 weeks, p = 0.044).…”
Section: Discussionmentioning
confidence: 99%
“…It has been taking advantage in the pain relief for the stereotactic radiosurgery to treat primary trigeminal neuralgia, which has high efficacy rate (88-96%), good quality life rate (about 85%) and low complication and recurrence rate (4-12%) (10,17). Compared with the classic vascular decompression of the trigeminal nerve, it was satisfied from less complication, efficiency rate and patients' satisfaction (7,11).…”
Section: Discussionmentioning
confidence: 99%
“…Matsuda (Matsuda 2008) in a series of 100 patients reports better pain control and lesser morbidity in patients treated with a proximal compared with those treated with a distal target. Conversely, Park (Park 2010) in a series of 39 patients found that a distal target was associated to more rapid response, better pain control and lower nerve morbidity. With the data available in the literature there are not clear differences in terms of clinical results between the two targets, then, considering any of these two targets as prognostic variable "scarce information with no clear trend or controversial findings" exist.…”
Section: Proximal Nerve Targetingmentioning
confidence: 94%